The Role of Collaboration in Overcoming MSME Challenges: Model Analysis to Improve Competitiveness and Sustainability - Setiadi, Sandi; Alhidayatullah; Maulana, Rizky (International Journal of Science and Society, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic development, but still face various challenges related to business sustainability amid market uncertainty and global competition. This study aims to analyze the role of collaboration in overcoming MSME challenges through its relationship with competitiveness, business policies, and business sustainability. The study uses a mixed approach, where quantitative data is analyzed using PLS-SEM, while qualitative data is obtained through interviews and focus group discussions (FGD) with MSME actors in Sukabumi Regency. The results show that collaboration and competitiveness have a positive effect on business sustainability, with business policy acting as a mediator that strengthens this relationship. Qualitative findings confirm that collaboration provides tangible benefits in the form of access to resources, innovation, and market networks, while competitiveness is built through product innovation, differentiation, and consistency in quality, which are translated into adaptive business policies. This study contributes to strengthening the Resource-Based View, Dynamic Capability, Stakeholder, and Institutional theories, while also providing practical implications for MSME actors, policymakers, and stakeholders in designing strategies to strengthen MSME sustainability systematically.